Sustaining Graduation: A Review of the CLM Programme in Haiti. (March 2015) - Pain, Chris; Vautravers, Emilie; Descieux, Alain
Abstract The Haitian NGO Fonkoze, with the support of Concern Worldwide, has been implementing the Chemin Lavi Miyo (CLM) Graduation Programme since June 2007 which targets the extreme poor in Haiti. Early results were promising, but questions prevailed around the sustainability of benefits. To address these concerns a further round of data collection was undertaken amongst a group of participants four years after graduation. Using a poverty scorecard to record information on housing quality, ownership of assets, household income and livelihoods, it was possible to assess that the mean level of asset‐holding remained higher than at baseline, but had slipped back slightly since graduation. Between graduation and the ex post survey 31 per cent continued on an upward trajectory, 39 per cent consolidated their position, but 30 per cent had slipped back considerably, suggesting the need for a more comprehensive social protection system than can be offered by an NGO‐implemented programme.